Master of Arts in Human Resources Management (MAHRM) - Kabale University (Kabale University, 2022)
The Master of Arts in Human Resources Management (MAHRM) program integrates up-to-date industry research to develop the critical thinking and problem-solving skills an HR professional needs. Our curriculum aligns with standards established by the Society for Human Resource Management (HRM), with an emphasis on development, strategy and communication. This programme instils you with innate problem-solving and critical thinking skills routed in ethics and a people-first approach. Graduate with a mastery of staffing, salary planning, negotiation, and more. The programme consists of 16 compulsory taught courses while the second part will involve a project inform of a Dissertation Writing.